2014
DOI: 10.1371/journal.pone.0084767
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIF prolyl-4-hydroxylases by FG-4497 Reduces Brain Tissue Injury and Edema Formation during Ischemic Stroke

Abstract: Ischemic stroke results in disruption of the blood-brain barrier (BBB), edema formation and neuronal cell loss. Some neuroprotective factors such as vascular endothelial growth factor (VEGF) favor edema formation, while others such as erythropoietin (Epo) can mitigate it. Both factors are controlled by hypoxia inducible transcription factors (HIF) and the activity of prolyl hydroxylase domain proteins (PHD). We hypothesize that activation of the adaptive hypoxic response by inhibition of PHD results in neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…Subsequently, HIF specifically binds to hypoxia response elements (HREs) in the promoters and enhancers of numerous genes followed by recruitment of p300/CBP resulting in enhanced transcription of HIF-responsive genes. 1,[8][9][10][11][12] A growing number of pre-clinical studies in rodents strongly suggests that activation of the HIF signaling pathway prior or shortly after ischemic stroke by application of low-molecular weight hydroxylase inhibitors 5,[13][14][15][16][17][18][19] or brief exposure to mild systemic hypoxia, [20][21][22][23] reduces tissue damage and increases functional recovery from ischemic stroke. However, as these therapeutic strategies unavoidably lead to pleiotropic activation of HIF signaling throughout all cell types of the central nervous system (CNS), it is difficult to draw conclusions about the definite significance of the HIF signaling pathway in neurons and their viability upon ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, HIF specifically binds to hypoxia response elements (HREs) in the promoters and enhancers of numerous genes followed by recruitment of p300/CBP resulting in enhanced transcription of HIF-responsive genes. 1,[8][9][10][11][12] A growing number of pre-clinical studies in rodents strongly suggests that activation of the HIF signaling pathway prior or shortly after ischemic stroke by application of low-molecular weight hydroxylase inhibitors 5,[13][14][15][16][17][18][19] or brief exposure to mild systemic hypoxia, [20][21][22][23] reduces tissue damage and increases functional recovery from ischemic stroke. However, as these therapeutic strategies unavoidably lead to pleiotropic activation of HIF signaling throughout all cell types of the central nervous system (CNS), it is difficult to draw conclusions about the definite significance of the HIF signaling pathway in neurons and their viability upon ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, we and others demonstrated that small-molecule PHD inhibitors, applied systemically, improve brain tissue damage and functional deficits in rodent models of ischemic stroke [4]. However, we also provided evidence that combined genetic loss of neuronal HIF-1α and HIF-2α in mice attenuates tissue injury in the early acute phase after cerebral ischemia, although it clearly impairs functional recovery at later stages indicating that activation of the HIF system by PHD suppressors can also have adverse effects [8].…”
Section: Oxygen Sensors and Neuronal Adaptation To Ischemia Hugo H Mmentioning
confidence: 83%
“…Both mediators are well known to be potent anti-apoptotic factors, which directly support neuronal survival. Accordingly, application of the PHD inhibitor FG-4497 strongly increased cell survival in pure neuronal cultures exposed to ischemic conditions [4]. In addition, neuronal PHD2 deletion resulted in increased expression of HIF-dependent glucose transporters and glycolytic enzymes [2].…”
mentioning
confidence: 97%
“…It is generally considered to be a heterogeneous and multifactorial disorder and caused by both conventional environmental risk factors and genetic factors [6,7] . It can cause acute neuronal death via oxygen and nutrient depletion, and result in disruption of the blood-brain barrier [8] . Acute ischemic stroke resulting from intracranial vessel occlusion is associated with high morbidity and mortality [9] .…”
Section: Introductionmentioning
confidence: 99%